A relação urbano-rural no contexto da metrópole: um enfoque nos assentamentos rurais da RMN - Lopes, Rosa Maria Rodrigues (2008)
The work however presented try to make an analysis of the relation urban-agricultural in the context of the process of metropolization of Natal. On the basis of this approach searched to argue the estruturation of the Brazilian urban space and the relation with the agricultural one, evidencing an academic debate little contemplated, in view of that the space transformations guided by Brazilian industrialization had earned as endorsement a mere urban direction, fact that neglected factors more complex than they for the urban-agricultural relation in the context of the urbanization and, more recently, of the metropolization. Another important factor in the construction of the work was the contextualization of the urbanization of the Rio Grande do Norte, as well as of the metropolization of Natal, where if the significant presence of an agricultural reality made an analysis of the configuration metropolitan in the present time displaying that also remains and reproduces the metropolis, fact that conditions and justifies the treatment of the reality metropolitan for the bias of the urban-agricultural relation. The approach of this relation was directed for the agricultural nestings of the Region Metropolitan of Natal (RMN), understood as fragments agricultural in the context of the metropolis, in view of that a tenuous correspondence of these nestings with the metropolis in the direction of its integration was observed. As methodology one used bibliographical survey in periodic and books and collected secondary data-collecting next to the IBGE and to the INCRA and still were directed a field research where interviews next to the seated ones had been carried through. In this direction, one evidenced that the metropolization also absorbs and even though it reproduces the ruralidade that if verifies in the RMN finishing for mining the idea of an urban one that it excludes the agricultural one. In the case of the RMN, we have agricultural and the urban one exactly if conforming in one space that is metropolitan